Síntomas del malestar psicológico con mayor frecuencia en empleados bancarios de la ciudad de Cali (2019)
The difficulties that arise in the labor context have been strongly addressed by the various branches of the social sciences, a good part of the studies carried out has been based on the account of the presence and physical characteristics of the Burnout syndrome, leaving aside the Specific effects of psychological distress. Objective. The research presented in this article had three objectives, the first is to identify the percentage of workers in the banking sector due to psychological distress; the second is to know the frequency with which the symptoms of psychological distress are presented and the third to identify the symptoms that occur most frequently in the employees of the banking sector of the city of Cali. Methodology. To obtain the information has become a quantitative issue, it has become known how often it has been shown in the employees of the banking sector. To obtain this result in a survey of 28 questions. Results. The rigidity of banking entities has generated a majority of the population in this sector by 53%, symptoms of psychological distress that occur with high frequency, such as: physical exhaustion, emotional exhaustion, guilt and difference with their personal values . However, 47% of the population has shown that they have implemented strategies to deal with the precariousness of the conditions in which they find themselves, minimizing the discomfort from the use of their own resources.